Ebola an evolving story - Lyons-Weiler, James (World Scientific, 2015)
The book is a narrative of the unfolding of the Ebola virus disease outbreak from a scientific view point. The author provides an analysis of the scientific basis of public health policies that have influenced the public's, and the medical community's, abilities to understand the virus and the disease. It will inform thousands of people of the nature of the virus, how it works, in terms they are likely to be able to understand. It will allow others to rapidly catch up with the story of Ebola.